Truncated skewed type III generalized logistic distribution: risk measurement applications - Theodossiou, Panayiotis (My University, 2020)
This article derives the moment functions of the truncated skewed type III generalized logistic (SGL). These are then applied in finance for the development of value at risk (VaR), expected shortfall (ES), and downside risk measures for investment returns and values. The SGL distribution provides and good fit to the empirical distribution of a representative set of long series of financial data. Moreover, the SGL generates accurate VaR measures.
Keywords: Downside risk; Expected shortfall; Flexible distributions; Truncated skewed generalized logistic; Value at risk